Comparison of Post Tooth Extraction Healing Using different Xenograft Materials -A Pilot Study. - Aldabbagh, Najla. (2017)
Abstract: Aim & Hypothesis: Ridge preservation procedures may be used to overcome the challenges of dimensional changes of the alveolar ridge following tooth extraction. Various materials are used alone or in combination in extraction sockets. The choice of bone material used influences the bone quality of the edentulous ridge. Micro CT provides a good insight into the bone healing and the bone quality in three dimensions. The aim of this pilot study was to evaluate and compare the bone density using three different bone xenografts in ridge preservation procedures. Materials & Methods: This randomized pilot study included ten patients requiring extraction of a non-restorable single rooted non-molar tooth. Comprehensive Periodontal and radiographic examination were performed prior to the extraction and before implant placement. Atraumatic tooth extraction was performed followed by ridge preservation surgery. Ten extraction sockets were randomly assigned to one of three groups: 1) Bio-Oss®, 2) Endobon® or 3) Equimatrix®. All grafted sockets were covered with a resorbable membrane (Mucograft) and partial primary closure was achieved. After 4 to 6 months, at the time of implant placement core biopsies were harvested using trephine burs. Samples were analyzed by Micro CT to compare bone density among the three different groups. Results: A slight difference was evident among the different parametric values between the Bio-Oss®, Endobon® and Equimatrix® groups. Bio-Oss® and Equimatrix® groups showed similar bone density but all were higher than the Endobon® group. The mean density for the Bio-Oss®, Endobon® and Equimatrix® groups were 1275.42, 1217.62 and 1258.72 respectively. The percentage of bone volume "BV/TV" was also higher in the Bio-Oss® and Equimatrix® groups when compared to the Endobon® group. Mean "BV/TV" was 0.2298 for the Bio-Oss®, 0.1287 for the Endobon® and 0.2556 for the Equimatrix®. However, significance testing was not performed due to the small sample size. Conclusion: Results from this pilot study are inconclusive due to the small number of subjects. Preliminary data obtained from this pilot study suggested that Bio-Oss® and Equimatrix® had higher mean bone density and mean bone volume when bone cores were analyzed by Micro CT. These results would be valuable to design future clinical trials with a larger sample size based on sample size calculations. It sets the stage for future studies in which statistical significant differences between the groups may be determined.; Thesis (M.S.)--Tufts University, 2015.; Submitted to the Dept. of Periodontology.; Advisor: Yong Hur.; Committee: Matthew Finkelman, Toshihisa Kawai, Bjorn Steffensen, Natalie Jeong, and Yumi Ogata.; Keywords: Health sciences, and Dentistry.